Madhab Prenialisme Study Kritis Filsafat Pendidikan Islam Terhadap Pengembangan Pendidikan Pancasila di Pondok Pesantren Salafiyah Bani Salimah - Ulfiyah; Wasehudin (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The flow of educational philosophy influences the progress of the nation, which is reflected in its philosophy, both originating from religious teachings and from the thoughts of leading philosophers. Perennialism, as a philosophical ideology, argues that values ​​from the past can be useful in the present, so people must maintain them today. This. This study aims to describe prennialism in Pancasila Education, the background of prennialism and understand the influence of prennialism on Pancasila Education. This study is a literature review using several literary approaches to explore the problem being studied. Preennialism is an ideology that advocates having eternal or eternal rules. In the 20th century, millennialism emerged as a progressive movement. They argue for a progressive perspective, which emphasizes new changes.